Bali 9 the untold story - Wockner, Cindy (Harper Collins, 2008)
In April 2005, nine young Australians were arrested in Bali on charges of drug trafficking. Known as the 'Bali 9', some members received the death penalty for their crimes; others are serving lengthy jail sentences. Journalists Cindy Wockner and Madonna King have pieced together the whole story, from arrest to jail to the harrowing final journey